Impact of pre-treatment technologies on soil aquifer treatment - Besançon, A.; Pidou, Marc; Jeffrey, Paul; Jefferson, Bruce; Le Corre Pidou, Kristell (IWA Publishing, 2016)
This study investigates the impact of pre-treatment options on the performances of soil columns simulating soil aquifer treatment (SAT). For this purpose a conventional activated sludge (CAS) process, a membrane bioreactor (MBR) and vertical flow reed beds were used as single units or in combination before SAT. The influent and effluent from each treatment train were monitored over three successive 6-month periods, corresponding to changes in the operational conditions of the MBR and CAS units from 6 days' sludge retention time (SRT) to 12 and 20 days. All the columns acted as efficient polishing steps for solids and bacteria. The column receiving effluent from the CAS system running at 6 days' SRT also presented high total nitrogen and total phosphorus removals, but this column was also associated with the lowest infiltration rates over that period. While the quality of the effluent from the column following the CAS process increased over 18 months of operation, the effluent quality of the columns receiving MBR effluent degraded. No correlations were found between variations in SRT of the MBR and CAS processes and the columns' performances. Overall, all columns, except the one receiving CAS effluent, underwent a reduction in infiltration rate over 18 months.
Keywords: conventional activated sludge; membrane bioreactor; reed beds; soil aquifer treatment